PENGARUH KOMITE AUDIT DAN KOMISARIS INDEPENDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2019 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to examine the effect of the audit committee and independent commissioners simultaneously or partially on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange 2015-2019. The population in this study are food and beverage companies that have data on audit committees, independent commissioners and stock prices listed on the Indonesia Stock Exchange 2015-2019, totaling 15 companies. This study uses secondary data sourced from www.idx.com. The data analysis technique used is path analysis with the help of the SPSS (Statistical Package for Social Science) program. The results of the study indicate that the audit committee and independent commissioners simultaneously affect stock prices. Partially, the audit committee has an effect on stock prices but has a negative relationship and independent commissioners have an effect on stock prices.Keywords: Audit Committee, Independent Commissioner, Stock Price.